Aquaporin water channels and endothelial cell function* - Verkman, AS (Blackwell Science Inc, 2002)
The aquaporins (AQP) are a family of homologous water channels expressed in many epithelial and endothelial cell types involved in fluid transport. AQP1 protein is strongly expressed in most microvascular endothelia outside of the brain, as well as in endothelial cells in cornea, intestinal lacteals, and other tissues. AQP4 is expressed in astroglial foot processes adjacent to endothelial cells in the central nervous system. Transgenic mice lacking aquaporins have been useful in defining their role in mammalian physiology. Mice lacking AQP1 manifest defective urinary concentrating ability, in part because of decreased water permeability in renal vasa recta microvessels. These mice also show a defect in dietary fat processing that may involve chylomicron absorption by intestinal lacteals, as well as defective active fluid transport across the corneal endothelium. AQP1 might also play a role in tumour angiogenesis and in renal microvessel structural adaptation. However, AQP1 in most endothelial tissues does not appear to have a physiological function despite its role in osmotically driven water transport. For example, mice lacking AQP1 have low alveolar-capillary water permeability but unimpaired lung fluid absorption, as well as unimpaired saliva and tear secretion, aqueous fluid outflow, and pleural and peritoneal fluid transport. In the central nervous system mice lacking AQP4 are partially protected from brain oedema in water intoxication and ischaemic models of brain injury. Therefore, although the role of aquaporins in epithelial fluid transport is in most cases well-understood, there remain many questions about the role of aquaporins in endothelial cell function. It is unclear why many leaky microvessels strongly express AQP1 without apparent functional significance. Improved understanding of aquaporin-endothelial biology may lead to novel therapies for human disease, such as pharmacological modulation of corneal fluid transport, renal fluid clearance and intestinal absorption.